Advances in Aerospace Guidance, Navigation and Control 2017
DOI: 10.1007/978-3-319-65283-2_36
|View full text |Cite
|
Sign up to set email alerts
|

SPARTAN: A Novel Pseudospectral Algorithm for Entry, Descent, and Landing Analysis

Abstract: In the last decades the theoretical development of more and more refined direct methods, together with a new generation of CPUs, led to a significant improvement of numerical approaches for solving optimal-control problems. One of the most promising class of methods is based on Pseudospectral Optimal Control. These methods not only provide an efficient algorithm to solve optimal-control problems, but also define a theoretical framework for linking the discrete numerical solution to the analytical one in virtue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Results were obtained with SPARTAN [20,24,26], a tool developed by the German Aerospace Center implementing pseudospectral methods, and are depicted in Figs. 4-8.…”
Section: Fig 3 Saturn V -Reconstruction Of Massflow For the S-ic Stamentioning
confidence: 99%
See 1 more Smart Citation
“…Results were obtained with SPARTAN [20,24,26], a tool developed by the German Aerospace Center implementing pseudospectral methods, and are depicted in Figs. 4-8.…”
Section: Fig 3 Saturn V -Reconstruction Of Massflow For the S-ic Stamentioning
confidence: 99%
“…In this paper we want to reconstruct three critical phases of the Apollo 11 mission by employing SPARTAN [19,24,25] a tool developed by the German Aerospace Center implementing multi-phase pseudospectral methods based on flipped Legendre-Gauss-Radau polynomials. For a more thorough description we suggest the reader to refer to [26], while in this context we will focus on the modeling of the phases of Apollo 11 mission, based on a critical comparison and integration of the different sources provided by NASA over the years.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that Eqs. (16) and (17) yield exact results for polynomials of order at most equal to 2n − 2 and 2n − 3 for fRPm and LPm, respectively [21]. Once again, the presence of the term…”
Section: Flipped Radau Pseudospectral Methods and Lobatto Pseudospementioning
confidence: 99%
“…Application examples using more sophisticated algorithms, such as the flipped Radau pseudospectral method (RPM), can be found in (Arslantas et al, 2014) and (Sagliano et al, 2017) for lunar landing and Earth re-entry guidance, respectively.…”
Section: Pseudospectral Methodsmentioning
confidence: 99%